Antibacterial activity of endophytic fungi from leaves of Indigofera suffruticosa Miller (Fabaceae) - Santos, Irailton Prazeres dos; Silva, Luís Cláudio Nascimento da; Silva, Márcia Vanusa da; Araújo, Janete Magali de; Cavalcanti, Marilene da Silva; Lima, Vera Lucia de Menezes (Frontiers in Microbiology, 2015)
Endophytic fungi were isolated from healthy leaves of Indigofera suffruticosa Miller, a medicinal plant found in Brazil, and used in folk medicine to treat various diseases. Among 65 endophytic fungi isolated, 18 fungi showed activity against at least one tested microorganism in preliminary screening, and the best results were obtained with the species Nigrospora sphaerica (URM-6060) and Pestalotiopsis maculans (URM-6061). However, after fermentation in liquid media (Potato Dextrose Broth, Saboraud, Malt Extract Broth and Eurimycin Production Medium), and in semisolid rice or corn culture media, only N. sphaerica demonstrated antibacterial activity (in Potato Dextrose Broth and in semisolid rice culture medium), as indicated by disk diffusion analysis. Methanolic extract of N. sphaerica (NsME) from rice culture medium and ethyl acetate extract of N. sphaerica (NsEAE) from supernatant of Potato Dextrose Broth exhibited antimicrobial against Gram-negative and Gram-positive bacteria. However the best result was observed against Staphylococcus aureus, with MIC 1.56 mg/mL and MBC 6.25 mg/mL for NsME and MIC 0.39 mg/ml and MBC 3.12 mg/mL for NsEAE. This study is the first report on antimicrobial activity of endophytic fungi residing in I. suffruticosa leaves, in which the fungus N. sphaerica demonstrated the ability to produce bioactive agents with pharmaceutical potential, and may provide a new lead in the pursuit of new biological sources of drug candidates.